Calendar, chronology, and worship : studies in ancient Judaism and early Christianity - Beckwith, Roger T. (Ancient Judaism and Early Christianity, 2005)
This book takes as its theme the related issues of calendar, chronology and worship, as they were conceived and practised in ancient Jewish and early Christian times. After a general discussion of the way the three issues are related, there follow six chapters on the calendar, first the standard Jewish calendar, then the Qumran calendar (giving particular attention to the Book of Enoch and the Temple Scroll) and finally the Christian calendar - both the standard Christian calendar and that observed by the Montanists. Three chapters on chronology come next, one of them offering a chronological solution to a puzzling calendrical problem in the Dead Sea Scrolls, another relating Jewish eschatological expectations to New Testament teaching, and a third examining the chronological calculations of the Hellenistic Jew Demetrius, the Testaments of the Twelve Patriarchs, and the Book of Jubilees. The three concluding chapters, on worship, include an investigation of the historical development of the Psalter and a careful survey of the relationship between ancient Jewish worship and early Christian. The book discusses a variety of issues that arise in modern biblical, intertestamental and patristic study, some neglected, some very controversial, and throws new light upon them.